To solve the equation \( 2x - 5 = 3(4x + 5) \), we can follow these steps in order:
-
Step 1: Distribute on the right side of the equation. \[ 2x - 5 = 12x + 15 \] (This involves applying the distributive property: \( 3(4x + 5) = 3 \cdot 4x + 3 \cdot 5 = 12x + 15 \))
-
Step 2: Subtract \( 12x \) from both sides. \[ 2x - 12x - 5 = 15 \] (This involves combining like terms to isolate \( x \) on one side)
-
Step 3: Combine like terms. \[ -10x - 5 = 15 \]
-
Step 4: Add 5 to both sides. \[ -10x = 20 \]
-
Step 5: Divide by -10. \[ x = -2 \]
So the completed ordered steps for the equation \( 2x - 5 = 3(4x + 5) \) are:
- Step 1: Distribute on the right side of the equation.
- Step 2: Subtract \( 12x \) from both sides.
- Step 3: Combine like terms on the left side.
- Step 4: Add 5 to both sides.
- Step 5: Divide by -10 to solve for \( x \).
Your output should reflect the step-wise approach to arriving at the solution.